Therapeutic Role of Animals: A Comprehensive Literature Review on the Prevalent Forms and Species in Animal-Assisted Interventions - Dorota Szewczyk; Jakub Fiega; Milena Michalska; Urszula Żurek; Zuzanna Lubaszka; Ewa Sikorska (Kazimierz Wielki University, 2023)
Animals have been valued and used to improve human physical and mental health since ancient times. Animal-assisted therapy (AAT) is a complementary approach to traditional medicine, involving trained animals. AAT can enhance cognition, commitment, character growth, and the learning process. Commonly used species in animal-assisted therapy include cats, dogs, horses, dolphins, and others. Feline-assisted therapy alleviates loneliness and stress, whereas canine-assisted therapy positively impacts emotions and overall well-being. Equine-assisted interventions benefit individuals with cognitive and motor disabilities. Dolphin-assisted therapy shows promise for conditions like autism and cerebral palsy. However, ethical concerns have arisen, particularly in children with behavioral disorders. Safety measures, adult supervision, and proper screening and hygiene practices are crucial in AAT programs. In conclusion, AAIs have a significant potential to enhance well-being and mental health across various contexts, but more research is needed to fully understand their effectiveness and safety in different settings and age groups. The existing literature consists of subjective accounts and inadequate methodologies.